2018
DOI: 10.1017/s1743921318005641
|View full text |Cite
|
Sign up to set email alerts
|

Central Stars of Planetary Nebulae in Galactic Open Clusters: Providing additional data for the White Dwarf Initial-to-Final-Mass Relation

Abstract: Accurate (<10%) distances of Galactic star clusters allow precise estimation of the physical parameters of any physically associated Planetary Nebula (PN) and also that of its central star (CSPN) and its progenitor. The progenitor's mass can be related to the PN's chemical characteristics and furthermore, provides additional data for the widely used white dwarf (WD) initial-to-final mass relation (IFMR) that is crucial for tracing the development of both carbon and nitrogen in entire galaxies. To date there is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The case of vd Bergh-Hagen 144 is interesting because its estimated metallicity of [Fe/H] = −0.53 −0.55 −0.48 is well below the expected solar value at that distance (R GC ∼ 8.5 kpc). There are two other articles where a similar markedly sub-solar metallicity was found for this cluster: Frinchaboy et al (2006b) and Fragkou et al (2019). In these studies the reported metallicity values are [Fe/H] = −0.51 ± 0.3 (spectroscopic metallicity from two stars) and [Fe/H] ≈ −0.40 (photometric estimate) 7 for Frinchaboy et al (2004) and Fragkou et al (2019), respectively.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The case of vd Bergh-Hagen 144 is interesting because its estimated metallicity of [Fe/H] = −0.53 −0.55 −0.48 is well below the expected solar value at that distance (R GC ∼ 8.5 kpc). There are two other articles where a similar markedly sub-solar metallicity was found for this cluster: Frinchaboy et al (2006b) and Fragkou et al (2019). In these studies the reported metallicity values are [Fe/H] = −0.51 ± 0.3 (spectroscopic metallicity from two stars) and [Fe/H] ≈ −0.40 (photometric estimate) 7 for Frinchaboy et al (2004) and Fragkou et al (2019), respectively.…”
Section: Resultssupporting
confidence: 66%
“…Both age and distance values for these two articles are very close to ours. Recently Fragkou et al (2019) suggested a slightly larger distance of ∼ 12 kpc, the value present in OC02 and WEBDA, and an age of about 0.66 Gyr.…”
Section: Discussionmentioning
confidence: 82%
“…Frinchaboy et al (2004b) andFragkou et al (2019). In these studies the reported metallicity values are [Fe/H]=-0.51±0.3 (spectroscopic metallicity from 2 stars) and [Fe/H]≈-0.40 (photometric estimate) 7 , forFrinchaboy et al and Fragkou et al respectively.…”
mentioning
confidence: 84%
“…Nevertheless, the confirmation of a PN associated to an open cluster, has a direct implication on the upper limit on the progenitor's mass. Fragkou et al (2019a) and Fragkou et al (2019b) have proved that the PNe PHR 1315−6555 and BMP J1613−5406 are physically linked to an open cluster. Consequently we have, for the first time, observational evidence that the upper limit of the initial stellar mass for the formation of a PN can be as high as M * 5.0 M ⊙ .…”
Section: Introductionmentioning
confidence: 99%